1999
DOI: 10.1002/(sici)1521-4141(199903)29:03<918::aid-immu918>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lectins can inducein vitro release of IL-4 and IL-13 from human basophils

Abstract: Dietary lectins, present in beans and other edible plant products, pose a potential threat to consumers due to their capacity to induce histamine release from basophils. In this study, we analyzed the capacity of 16 common, in particular dietary, lectins to induce human basophils to secrete IL-4 and IL-13, the key promoters of Th2 responses and IgE synthesis. Several of the lectins, especially concanavalin A, lentil lectin, phytohemagglutinin, Pisum sativum agglutinin and Sambucus nigra agglutinin, triggered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(15 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The possibility that IPSE acts as a lectin cannot be excluded, but its sequence does not show any similarity with known animal or plant lectins. Furthermore, although several lectins can activate basophils (32), the concentrations required are in the g/ml range. In contrast, the possibility that IPSE is a B cell superantigen requires consideration; B cell superantigens, such as HIV-1 gp120, protein Fv, and protein L (33,34), 2 can bind to IgE and, as multivalent molecules, can activate basophils, resulting in the release of IL-4 and IL-13.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that IPSE acts as a lectin cannot be excluded, but its sequence does not show any similarity with known animal or plant lectins. Furthermore, although several lectins can activate basophils (32), the concentrations required are in the g/ml range. In contrast, the possibility that IPSE is a B cell superantigen requires consideration; B cell superantigens, such as HIV-1 gp120, protein Fv, and protein L (33,34), 2 can bind to IgE and, as multivalent molecules, can activate basophils, resulting in the release of IL-4 and IL-13.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , it has been demonstrated that incubation with lectin from red kidney bean lead to T cell proliferation and increased cytokine production (7). Haas et al demonstrated that certain dietary lectins can cause IL-4 and IL-13 release from basophils (8), while Gong et al demonstrated that plant lectins can activate NLRP3 inflammasome in macrophages, although at concentrations outside of normal physiological conditions (9). Recently it has been shown that certain lectins can activate toll-like receptors (TLRs) in a distinct, yet comparable, fashion to activation by pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, WGA has an important effect on the immune system, as it can stimulate the immune system inducing the production of pro-inflammatory cytokines both in human peripheral blood mononuclear cells (PBMC) [50,51] and in animals [52,53].…”
Section: Wheat Germ Agglutinin (Wga)mentioning
confidence: 99%